Body Density Disparities among Female Athletes of Different Running Events Estimated by 7-Site Skinfold Equation - Gedefaw (Ph.D), Haileyesus; Tesema, Gashaw; Dessalegn, Tesfaye (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2024)
The study aimed at investigating body density disparities among female athletes specializing in different running event categories such as, short-distance sprints, middle-distance runs, and long-distance endurance races. Body density of athletes analyzed using the 7-site skin-fold equation. Anthropomorphic measurements were conducted following the guidelines of the International Society for the Advancement of Kin anthropomorphic, and body density estimated from it. Descriptive statistics, one-way Analysis of Variance, and post hoc tests employed to explore differences among the groups. Results indicate significant disparities in body density found among groups, underscoring the importance of training programs designed for athletes based on their event category.